The transparency of the family: A study on conservative family profiles on Instagram - Gültekin, Metin; Yildiz, Ahmet (IGI Global, 2025)
While modern conservative individuals act on the basis of beliefs and traditions, the development of communication technologies and post-fordist lifestyles have increased the flexibility of societies. This flexibility is also reflected in family structures and the roles of individuals. The traditional family structure has undergone major transformations in the industrial and information ages. Social media platforms such as Instagram allow individuals to construct and present their lives, making the lives of conservative families visible. However, the fact that Instagram is a digital stage suggests that the life presented may not reflect true conservative values. Conservatism's emphasis on privacy increases the interest in social media representations and shapes the quality of content. © 2025, IGI Global Scientific Publishing. All rights reserved.
Keywords: Communicationtechnology; Conservative value; Family structure; Information age; Media representation; Quality of contents; Social media; Social media platforms